Identifying pathophysiological bases of disease in COVID-19 - Goldin, Carla Jimena (2020)
COVID-19 is an infectious disease caused by the SARS-CoV-2 virus that can affect lung physiology encompassing a wide spectrum of severities, ranging from asymptomatic and mild symptoms to severe and fatal cases; the latter including massive neutrophil infiltration, stroke and multiple organ failure. Despite many recents findings, a clear mechanistic description underlying symptomatology is lacking. In this article, we thoroughly review the available data involving risk factors, age, gender, comorbidities, symptoms of disease, cellular and molecular mechanisms and the details behind host/pathogen interaction that hints at the existence of different pathophysiological mechanisms of disease. There is clear evidence that, by targeting the angiotensin-converting enzyme II (ACE2) –its natural receptor–, SARS-CoV-2 would mainly affect the reninangiotensin-aldosterone system (RAAS), whose imbalance triggers diverse symptomatology-associated pathological processes. Downstream actors of the RAAS cascade are identified, and their interaction with risk factors and comorbidities are presented, rationalizing why a specific subgroup of individuals that present already lower ACE2 levels is particularly more susceptible to severe forms of disease. Finally, the notion of endotype discovery in the context of COVID-19 is introduced. We hypothesize that COVID-19, and its associated spectrum of severities, is an umbrella term covering different pathophysiological mechanisms (endotypes). This approach should dramatically accelerate our understanding and treatment of disease(s), enabling further discovery of pathophysiological mechanisms and leading to the identification of specific groups of patients that may benefit from personalized treatments.